Culture Technique, Growth and Comparative Nutritional Analysis of Perinereis nuntia in Southeast Region of Bangladesh - Chowdhury, Methila; Shikha, Shanjida Islam; Miah, Shahin; Faisal, Md; Khatoon, Helena (Research in Agriculture Livestock and Fisheries, 2025)
The culture methods and nutritional analysis of Perinereis nuntia, a polychaete species commonly used as feed for carnivorous aquatic animals, including fish and marine shrimp, were thoroughly examined. Perineiris nuntia is an endogenous polychaete species of Thailand that is commercially cultured in different hatcheries for rearing shrimp brood stock in Bangladesh. Larvae are reared in a direct saline water supply from the Bay of Bengal in three different stages. The cultivation process includes various stages, including egg collection, hatching, larval rearing, adult nurturing, brood stock management, and harvest. P. nuntia exhibited distinct developmental phases (monotrochophore, trochophore, metatrochophore, and nectochaete) each with specific feeding requirements. The polychaetes had segmented bodies with parapodia; the females carried green eggs, while the males carried white sperm. Adults were fed at 200–300 microns, whereas larvae were fed at 5–50 microns. Brood death after gamete discharge was a characteristic of tidal-influenced reproductive activity. It was noted that during fertilization, the male to female sex ratio was maintained at 1:5. The total development of a polychaete required seven to eight months. The culture method yields 3-4 kg of polychaete per square meter area of the culture tank or 77 kg from each culture tank. According to proximate composition study, juvenile polychaetes had higher nutrient content than adults (63.58% protein, 10.03% lipid, 8.97% ash, and 1.49% moisture). The result suggests that the polychaete juveniles of three to four months contain a greater nutritional value or there is a significant difference in protein and lipid content Farmers can short the culture period for supplying feed to the shrimp broodstock to fulfill protein demand. In order to provide useful information for both scientific research and commercial applications, this study was to clarify the viability and difficulties related to P. nuntia growing. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 307-318